4-Aminosalicylic Acid-based Hybrid Compounds: Synthesis and In vitro Antiplasmodial Evaluation - Nqoro, Xhamla; Jama, Siphesihle; Morifi, Eric; Aderibigbe, Blessing A. (Letters in Drug Design & Discovery, 2021)
Background: Malaria is a deadly and infectious disease responsible for millions of death worldwide, mostly in the African region. The malaria parasite has developed resistance to the currently used antimalarial drugs, and it has urged researchers to develop new strategies to overcome this challenge by designing different classes of antimalarials. Objectives: A class of hybrid compounds containing 4-aminosalicylic acid moiety was prepared via esterification and amidation reactions and characterized using FTIR, NMR and LC-MS. In vitro antiplasmodial evaluation was performed against the asexual NF54 strain of P. falciparum parasites. Methods: In this research, known 4-aminoquinoline derivatives were hybridized with 4- aminosalicylic acid to afford hybrid compounds via esterification and amidation reactions. 4- aminosalicylic acid, a dihydrofolate compound inhibits DNA synthesis in the folate pathway and is a potential pharmacophore for the development of antimalarials. Results: The LC-MS, FTIR, and NMR analysis confirmed the successful synthesis of the compounds. The compounds were obtained in yields in the range of 63-80%. The hybrid compounds displayed significant antimalarial activity when compared to 4-aminosalicylic acid, which exhibited poor antimalarial activity. The IC50 value of the most potent hybrid compound, 9 was 9.54±0.57 nm. Conclusion: 4-aminosalicylic has different functionalities, which can be used for hybridization with a wide range of compounds. It is a potential pharmacophore that can be utilized for the design of potent antimalarial drugs. It was found to be a good potentiating agent when hybridized with 4- aminoquinoline derivatives suggesting that they can be utilized for the synthesis of a new class of antimalarials.
Keywords: 4-aminosalicylic acid